Enhanced a novel approach for smoothing data in modelling and decision-making problems under fuzziness - Hamiden Khalifa; Seyyed Edalatpanah; Darko Bozanic (Computational Algorithms and Numerical Dimensions)
Smoothing (filtering) of data is a major problem in engineering and science. In this paper, the smoothing of data arising in modelling and decision-making problems is considered. Firstly, the conventional smoothing and filtering problem and its extension to a fuzzy situation are introduced.